KONSTRUKSI INKLUSI SOSIAL BAGI KELOMPOK MINORITAS DALAM PERSPEKTIF FIKIH SIYASAH KONTEMPORER DI INDONESIA - Mochammad Hesan (Qolamuna : Jurnal Studi Islam, 2025)
Social inclusion of minority groups remains a critical issue in Indonesia’s plural society. This study aims to examine the construction of social inclusion for minority groups from the perspective of contemporary fiqh siyasah and its relevance to Indonesia’s constitutional and socio-political context. This research employs a qualitative approach using a normative-critical method through an extensive literature review of contemporary fiqh siyasah, maqāṣid al-sharī‘ah, public policy documents, and peer-reviewed scholarly works published within the last five years. Data were analyzed using content analysis and a normative-contextual approach. The findings indicate that the principles of justice (al-‘adl), equality (al-musāwah), and public interest (al-maṣlaḥah) within fiqh siyasah are substantively aligned with modern concepts of social inclusion. However, persistent social exclusion of minority groups in Indonesia is largely driven by limitations in contextual interpretation and implementation of Islamic political jurisprudence. Therefore, a reconstruction of fiqh siyasah grounded in maqāṣid al-sharī‘ah is essential to strengthen minority protection and promote inclusive public policies. This study concludes that contemporary fiqh siyasah can serve as a normative and ethical framework for fostering inclusive, just, and sustainable governance in Indonesia. Keywords: social inclusion; minority groups; fiqh siyasah; maqāṣid al-sharī‘ah; Indonesia